Assessing sport tourists’ overall satisfaction: a study of ISTAF super series tournament - Zarei, Azadeh; Yusof, Aminuddin (2014)
Costumer’ satisfaction has been publicized as successful sport business and marketing and improves the strategic planning of sport event performance. Using Leiper’s (1990) Tourist Attraction System Model, this paper examined satisfaction level from the perspective of 316 sport tourists comprised of domestic (n=224) and foreign sport tourists (n=92) attending ISTAF Super Series. Findings from t-test analysis show that no difference significantly was identified among domestic and foreign sport tourists. The findings provided support for the Sepak takraw event as a potential area of sustainable tourism development in terms of social impact within small-scale sport-tourism context.